Digital Pedagogy Practices in Teachers at Aisyiyah Smart Kids Center Jumantono - Astuti, Heni; Fitriyah, Qonitah Faizatul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to enhance teachers’ digital pedagogical competence by equipping them with up‑to‑date technological skills, enabling them to operate digital tools effectively in their teaching practice and meet the demands of 21st‑century learning. Methodology: A qualitative literature‑review approach was employed, involving systematic searches across academic and professional sources, followed by critical analysis and synthesis of findings related to teachers’ use of technology in education. Results: The review indicates that many Indonesian teachers remain unprepared for integrating technology into instruction, often relying on conventional materials. To bridge this gap, teachers must develop digital pedagogical competence—an amalgam of technological, pedagogical, and content knowledge—to design creative, innovative learning experiences aligned with modern digitalization trends. Applications/Originality/Value: By highlighting the critical role of digital pedagogical competence, this study provides a theoretical foundation and practical roadmap for teacher‑training programs, curriculum developers, and policymakers aiming to empower educators to thrive in a rapidly digitalizing world and to foster more engaging, technology‑rich classrooms.